2015
DOI: 10.1039/c4sc02130d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically selective inhibitors of histone deacetylase 2 (HDAC2) as cognition enhancers

Abstract: Kinetically selective inhibitors of HDAC2 enhanced learning and memory in a CK-p25 mouse model of neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 40 publications
(69 reference statements)
4
83
0
Order By: Relevance
“…The Hdac2 RNAi experiments were complemented by treatment with four small molecule HDAC inhibitors with different specificities: trichostatin A (TSA), a HDAC class I and II inhibitor (Yoshida et al, 1990) (Figure S6A); RGFP966, a HDAC class I inhibitor (Chou et al, 2008) (data not shown); and both BRD4884 and BRD6688, which are specific HDAC2 inhibitors (Wagner et al, 2015) (Figures S5I–S5L). All of these small molecules effectively reduced the expression of neural markers in intact polyps and inhibited head regeneration following decapitation (Figures 5L, S5M and S6B-S6L).…”
Section: Resultsmentioning
confidence: 99%
“…The Hdac2 RNAi experiments were complemented by treatment with four small molecule HDAC inhibitors with different specificities: trichostatin A (TSA), a HDAC class I and II inhibitor (Yoshida et al, 1990) (Figure S6A); RGFP966, a HDAC class I inhibitor (Chou et al, 2008) (data not shown); and both BRD4884 and BRD6688, which are specific HDAC2 inhibitors (Wagner et al, 2015) (Figures S5I–S5L). All of these small molecules effectively reduced the expression of neural markers in intact polyps and inhibited head regeneration following decapitation (Figures 5L, S5M and S6B-S6L).…”
Section: Resultsmentioning
confidence: 99%
“…HDAC inhibitors of this type may have potential for preventing and controlling neurodegeneration and cognitive dysfunction [46]. Provocative recent studies reveal that overactivity of HDAC2 -thought to be typical of Alzheimer's disease [47] -impairs long-term potentiation and synaptic plasticity by down-regulating transcription of numerous proteins, including CREB and brain-derived neurotrophic factor (BDNF), that participate in these processes; conversely, inhibition of HDAC2 reverses cognitive dysfunction in mouse models of Alzheimer's [47][48][49][50][51][52]. Excessive deacetylation of histones may also play a pathogenic role in Parkinson's disease; in this disorder, alpha-synuclein accumulates within the nucleus and binds to histone H3, suppressing its acetylation [53,54].…”
Section: Ketones Modulate Protein Acetylationmentioning
confidence: 97%
“…Some of those that were developed most recently and are not yet commercialized have better tissue penetration and HDAC1 and HDAC2 selectivity than SAHA (Wagner et al., 2015). We suggest that these compounds hold promise for providing therapeutic benefits in cases of progressive hearing loss caused by gain-of-function mutations in REST .…”
Section: Discussionmentioning
confidence: 99%